2004
DOI: 10.1007/s11920-004-0061-5
|View full text |Cite
|
Sign up to set email alerts
|

Developmental precursors of psychosis

Abstract: Subtle developmental (motor, emotional, cognitive, and behavioral) abnormalities are often present in apparently healthy individuals who later develop psychosis, suggesting that some aspects of causation are established before overt psychosis. These impairments may restrict information processing and social achievements years before manifesting psychosis. The main known risk factors in the development of schizophrenic psychosis are genetic factors, pregnancy and delivery complications, slow neuromotor developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Also, a recent study found no direct effects of obstetric complications and developmental delays on the risk of developing schizophrenia whereas a cumulative effect of both factors was found to be significantly associated (Clarke et al, 2011). It is thought that obstetric factors might create a neural diathesis during brain development, which in turn may increase the risk for psychosis (Goldstein et al, 2000;Isohanni et al, 2004;Mrad et al, 2010). This aspect was, however, not explicitly tested in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…Also, a recent study found no direct effects of obstetric complications and developmental delays on the risk of developing schizophrenia whereas a cumulative effect of both factors was found to be significantly associated (Clarke et al, 2011). It is thought that obstetric factors might create a neural diathesis during brain development, which in turn may increase the risk for psychosis (Goldstein et al, 2000;Isohanni et al, 2004;Mrad et al, 2010). This aspect was, however, not explicitly tested in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…Insofar as childhood psychopathology is likely to be a proxy for premorbid adjustment, we found comparatively poorer function prior to onset of bipolar disorder to be an important predictor of outcomes. Poor premorbid function has been studied much more extensively in schizophrenia than in bipolar disorder (61–63). The former condition is considered to be neurodevelopmental, and impaired cognitive processing and its effect on function has been demonstrated frequently (64–66).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological soft signs, impairment on tests of fine-motor coordination and other neuromotor functions, and abnormal involuntary movements have been demonstrated in antipsychotic-naïve patients, and neuromotor abnormalities have been observed in children destined to develop schizophrenia as early as 2 years of life (Walker et al, 1994; Isohanni et al, 2004). Given that G/R infection was not associated with processing speed in the present study, which has a strong psychomotor component, the findings of the present study suggest that the neuromotor abnormality was relatively specific to fine-motor coordination.…”
Section: Discussionmentioning
confidence: 99%